Itogi . Itogi . Results . Итоги - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. An accident at the Zaporozhye nuclear power plant; political and economic crisis in Ukraine; constitutional reform in Russia; discussion of the law "On Elections to the Supreme Soviet of the Russian Federation." Featured in the program: IAkovlev, Aleksandr Nikolaevich (Doctor of Juridical Sciences); Kuchma, Leonid Danylovych (Prime Minister of Ukraine); Satarov, Georgii (Political Scientist); Butunin, IUrii (Doctor of Juridical Sciences); Sheinis, Viktor Leonidovich (Political Scientist); Kravchuk, Leonid Makarovich (President of Ukraine) Contributors: Kiselev, Evgenii (Anchor) Series description: Weekly information and analytical program hosted by Evgenii Kiselyov. Broadcasted from January 3, 1992 till June 15, 2003. The program discussed and analyzed major political news and regularly invited to the show prominent politicians, public and cultural figures. Чрезвычайное происшествие на Запорожской АЭС; политический и экономический кризис в Украине; конституционная реформа в России; обсуждение закона "О выборах в Верховный Совет Российской Федерации.". В программе участвуют: Яковлев, Александр Николаевич (Доктор юридических наук); Кучма, Леонид Данилович (Премьер-министр Украины); Сатаров, Георгий (Политолог); Бутунин, Юрий (Доктор юридических наук); Шейнис, Виктор Леонидович (Политолог); Кравчук, Леонид Макарович (Президент Украины) Создатели: Киселев, Евгений (Ведущий/Ведущая) Описание серии: Еженедельная авторская информационно-аналитическая передача Евгения Киселёва, выходившая с 3 января 1992 по 15 июня 2003 года. В программе обсуждались и анализировались главные политические новости, события и тенденции политической жизни, регулярно выступали известные политики, общественные и культурные деятели.